Proteomic Analysis Reveals GLUT1 to be a Novel Discriminating Marker of Human Arterial Endothelium In vivo and loss of Venous Identity in Cell Culture - Richardson MR; Patrick Cahan; Xianyin Lai; Nutan Prasain; Mervin C Yoder; Frank A Witzmann (Open Journal of Proteomics and Genomics - Peertechz Publications, 2016)
Despite greatly improved understanding of endothelial heterogeneity, the number of molecules discriminating human arterial and venous endothelium remains limited. Indeed, there have been few reports validating markers proposed in animal model studies in freshly isolated human tissues. We report here the global characterization of freshly isolated human umbilical arterial and venous endothelial cell (HUAECs and HUVECs) plasma membrane proteins using an experimentally validated label-free quantitative LC-MS/MS platform. ECs were harvested by enzymatic digestion and purified by flow cytometry (CD31+, CD45-) prior to quantitative analyses. Following plasma membrane fractionation, we identified 4,300 proteins with high confidence using LC-MS/MS. GLUT1, an important regulator of endothelial function, was found to be up regulated in HUAECs 2.6 fold at the protein level and confirmed at the mRNA level using qRT-PCR. Using tissue immunohistochemistry, we discovered that GLUT1 expression was restricted to the cell surface in human arterial endothelium using umbilical cord and adult peripheral vascular sections. Importantly, GLUT1 mRNA levels decreased 20 fold in cultured arterial ECs within 48hrs of culture and continued to decline for 12 days in vitro. Principal Component Analyses demonstrated a profound effect of cell culture on protein expression signatures with cultured HUVECs, fresh HUVECS, and fresh HUAECs equally distinct. GLUT1 expression serves as a robust discriminator of arterial versus venous ECs in vivo and marks a loss of venous EC identity in vitro.